DETERMINANTS OF ANTIRETROVIRAL THERAPY ADHERENCE AMONG PEOPLE LIVING WITH HIV IN NORTH SUMATERA, INDONESIA - Hutapea, Lidya; Widyawati, Tri; Rahmawaty Lubis, Rodiah; M. Ichwan, M. Ichwan; Isti Ilmiati Fujiati, Isti Ilmiati Fujiati (Jurnal Kesehatan - STIKes Prima Nusantara, 2026)
Background: Human Immunodeficiency Virus (HIV) continues to pose a major global public health challenge, especially in low and middle income countries. Sustained adherence to Antiretroviral Therapy (ART) is fundamental to achieving viral suppression, preventing disease progression, and reducing transmission. Despite advances in treatment availability, suboptimal adherence continues to hinder optimal clinical outcomes. Aims: This study aimed to examine the key determinants influencing ART adherence among people living with HIV (PLHIV) in North Sumatra, Indonesia. Methods: A quantitative cross-sectional study was conducted from April to December 2024 at Dr. Ferdinand Lumbantobing General Hospital, Sibolga City. All 88 PLHIV receiving ART during the period were recruited using total sampling. Data were collected via structured questionnaires and analyzed using univariate analysis, chi-square tests, and multivariate logistic regression to identify significant adherence predictors. Results: ART adherence was significantly associated with treatment-related knowledge, family support, healthcare provider support, and access to healthcare facilities (p < 0.05). Multivariate logistic regression revealed that treatment knowledge was the most influential determinant of adherence, followed by family support, healthcare provider support, and healthcare accessibility. Conclusion: ART adherence in this tropical setting is shaped by a dynamic interplay of individual understanding and social and healthcare system support. Strengthening patient education, fostering family engagement, and improving access to healthcare services are essential strategies for sustaining treatment adherence over time. Future longitudinal research is warranted to explore adherence trajectories and evaluate targeted intervention models